GILLNET SELECTIVITY PARAMETERS FOR COMMERCIALLY IMPORTANT SPECIES, LABEO ROHITA IN A TROPICAL RESERVOIR, KERALA, INDIA - K. M., SANDHYA; R, SARANYA; R. K. , AMRUTHTA; B., MANOJ KUMAR; THOMAS, SALY N. (Journal of the Inland Fisheries Society of India, 2025)
The selectivity of fishing gear characterizes its capacity and efficiency in capturing fish. This knowledge helps in selecting the appropriate mesh size to suit the available fish population. The present study aims to estimate the gillnet selectivity parameters of a commercially important fish species, Labeo rohita, from a tropical reservoir in Meenkara, Kerala, India. The study was conducted from September 2019 to February 2020 through experimental fishing using gillnets of different mesh sizes (120, 130, 140, and 150mm) of identical design and dimensions. Selectivity parameters were estimated using Holt’s indirect method. The estimated optimum selection length of L. rohita for three different mesh sizes (120, 130, and 140mm) was 46.56, 50.44, and 54.32cm, and the common selection factor (SF) was 3.88. The estimated optimum mesh size of 127 mm was found to be ideal for the commercial exploitation of L. rohita in the Meenkara reservoir. The gillnet selectivity estimates obtained in the present study will be beneficial to increase the likelihood of capturing targeted size classes as well as better management of the L. rohita fishery in Meenkara reservoir.